Odpowiedź :
[tex]a) 5 \frac{1}{9} - 1 \frac{7}{9} +4\frac{8}{9} - 2 \frac{2}{9} = 3\frac{3}{9} +4\frac{8}{9} - 2 \frac{2}{9} = 8\frac{2}{9} - 2 \frac{2}{9} = 6[/tex]
[tex]b) 3\frac{5}{7} -1\frac{6}{7} +15\frac{4}{7} = 1\frac{6}{7} +15\frac{4}{7} = 17\frac{3}{7}[/tex]
[tex]c) 7 \frac{9}{15} +3\frac{2}{15} -4\frac{1}{15} -\frac{6}{15} = 10 \frac{11}{15} -4\frac{1}{15} -\frac{6}{15} = 6\frac{10}{15} -\frac{6}{15} =6\frac{4}{15}[/tex]
Odpowiedź:
[tex]a)\ \ 5\frac{1}{9}-1\frac{7}{9}+4\frac{8}{9}-2\frac{2}{9}=5\frac{1}{9}+4\frac{8}{9}-1\frac{7}{9}-2\frac{2}{9}=9\frac{9}{9}-3\frac{9}{9}=10-4=6\\\\\\b)\ \ 3\frac{5}{7}-1\frac{6}{7}+15\frac{4}{7}=3\frac{5}{7}+15\frac{4}{7}-1\frac{6}{7}=18\frac{9}{7}-1\frac{6}{7}=17\frac{3}{7}\\\\\\c)\ \ 7\frac{9}{15}+3\frac{2}{15}-4\frac{1}{15}-\frac{6}{15}=10\frac{11}{15}-4\frac{1}{15}-\frac{6}{15}=6\frac{10}{15}-\frac{6}{15}=6\frac{4}{15}[/tex]